(untitled) (Community Based Medical Journal, 2023)
A randomized prospective single blind trial was conducted in the Department of Anaesthesia, Analgesia, Palliative and Intensive Care Medicine, Dhaka Medical College Hospital, Dhaka, Bangladesh, between July 2021 and February 2022, to compare the effects of intravenous pethidine and nalbuphine hydrochloride combating epigastric pain and discomfort during mopping of intraperitoneal blood in lower uterine caesarean section (LUCS) operation. A total of 120 women participated in the study. They were randomly divided into two groups: group A (n=60) received intravenous diluted (with normal saline) 20-25 mg of pethidine, while group B (n=60) received intravenous diluted 10-20 mg of nalbuphine hydrochloride. There were no differences observed in mean age, weight, height, and duration of operation between two groups (P>0.05). However, participants of group B reported less or no epigastric pain and discomfort during mopping of intraperitoneal blood than that of group A (P<0.05), i.e., episode and intensity of pain measured by using visual analogue scales indicated that nalbuphine hydrochloride has a longer duration of action than pethidine. Our study revealed that intravenous diluted nalbuphine hydrochloride works better than pethidine to minimize epigastric pain and discomfort during mopping of intraperitoneal blood in lower uterine caesarean section (LUCS) operation. CBMJ 2023 January: Vol. 12 No. 01 P: 81-86